Designing low cost water haresting system for Bundelkhand region and rejuvinating Haveli system - CGIAR Research Program on Water, Land and Ecosystems (2017)
Water harvesting protocol for the study region was developed and piloted in three villages. The pilot showed large benefit by decentrilized water harvesting practices.